2017
DOI: 10.1177/0164027517717044
|View full text |Cite
|
Sign up to set email alerts
|

Aging in Place in Every Community: Social Exclusion Experiences of Parents of Adult children With Autism Spectrum Disorder

Abstract: This article offers an examination of aging processes of lifelong caregivers and the possibilities for social exclusion place experienced by parents of adult children with autism spectrum disorder (ASD). This study of parental caregivers ( n = 51) sheds light on how enduring caregiving roles can lead to social exclusion in three ways: misunderstanding of ASD and stigma, the complexity of the caregiving roles, and impact on daily routines including challenges with long-term planning for both the adult children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 38 publications
0
35
0
1
Order By: Relevance
“…Extant evidence indicated that parental caregivers were more likely to report missing out on a normal way of life, experience social disconnectedness from relatives and friends, and feel unsupported by systems and society at large [ 28 , 29 ]. Time dependence is the perception of burden secondary to the time restrictions faced by parents because of the enduring and lifelong demands of caregiving for adult children [ 24 , 30 ]. Time devoted to caregiving can reduce opportunities to associate with friends, family members, and spouses, and can restrict parent caregivers’ potential for pursuing career, leisure, and community interaction opportunities [ 7 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Extant evidence indicated that parental caregivers were more likely to report missing out on a normal way of life, experience social disconnectedness from relatives and friends, and feel unsupported by systems and society at large [ 28 , 29 ]. Time dependence is the perception of burden secondary to the time restrictions faced by parents because of the enduring and lifelong demands of caregiving for adult children [ 24 , 30 ]. Time devoted to caregiving can reduce opportunities to associate with friends, family members, and spouses, and can restrict parent caregivers’ potential for pursuing career, leisure, and community interaction opportunities [ 7 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with developmental disabilities, particularly autism spectrum disorder (ASD), often experience stigmatising public reactions (Ali et al, 2012;Broady et al, 2017;Eaton et al, 2016;Marsack et al, 2018;Tudose et al, 2017). This stigma can spill over to care providers who, by virtue associating with the stigmatised person, also experience negative reactions from the public (Abojabel et al, 2016;Koshorke et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For example, caregivers of individuals with ASD experience greater stigma than do caregivers of individuals with intellectual or physical disabilities [25]. Previous studies on self-stigma of families of individuals with ASD show that parents exhibit difficulties regarding self-stigma [26,27], repeated experiences of guilt and remorse [28], lack of knowledge of their surroundings [29], and social exclusion [30]. They may also hide the behavioral characteristics of their children [31] and how they deal with them [32].…”
Section: Self-stigma Of Familiesmentioning
confidence: 99%
“…Evidence from the structural aspects supporting the validity of the scale's construct [39] was confirmed for all factors. When compared with the self-stigma theory [18,19], the social misunderstanding construct has not been previously seen in the self-stigma theory, although, previous studies on self-stigma of families of individuals with ASD show that parents experience various social misunderstandings, including difficulties that are related to self-stigma [29,30]. Therefore, it was considered clinically important to include these sub-factors.…”
Section: Structural Validitymentioning
confidence: 99%